Enabling Online Equity Crowdfunding: Understanding the Legal Approval Process Across Four Countries - Iurchenko, Denis; Petty, Jeffrey S.; Shang, Carrie; Block, Joern (Senate Hall, 2020)
Affecting regulation is difficult for any firm, but it requires strenuous efforts for those operating in emerging industries. In this study, we seek to understand the complex process through which equity crowdfunding has become adopted in four Commonwealth countries following the passage of equity crowdfunding regulations in the US. We use extensive archival data to analyze how social discourse, as well as institutional environment, have made an impact on governmental regulatory decisions concerning the new model of venture finance. We find that the adoption of equity crowdfunding is a complex process shaped by firms' interactions with various interested parties, especially regulators and other relevant state actors. Based on the analysis, we propose several conditions that may increase the probability of legalization, one of which is complementarity with the goals of key stakeholders. This study contributes to the literature on equity crowdfunding, new industry emergence as well as to a broader stream of research on policy diffusion.
Keywords: entrepreneurship|new industry emergence